The global environment, natural resources, and economic growth - Greiner, Alfred; Semmler, Willi (Oxford : Oxford University Press, 2008)
Global growth, in particular high economic growth rates, implies a fast depletion of resources. Thus, this book deals with the impact on the environment and the effect of the exhaustive use of natural resources on economic growth and welfare of market economies.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Economic development -- Environmental aspects; Pollution -- Economic aspects; Natural resources -- Management